1994
DOI: 10.1029/94ja01232
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sudden impulses on currents in the auroral ionosphere under northward interplanetary magnetic field conditions: A case study

Abstract: We examine the response of auroral magnetic records to the passage of an interplanetary shock at a time when the interplanetary magnetic field was northward. We restrict our attention solely to the sector within 3 hours of local magnetic midnight for a single case selected when a bursty bulk flow event was recorded in the near tail by ISEE 2. Over most of the nightside at high latitudes only a weak disturbance if any is seen. At lower latitudes a plateau is seen in the H component, coincident with the bursty b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 9 publications
1
12
0
Order By: Relevance
“…They also investigated effects of speed and direction of IP shocks on SSC rise times and found that the faster IP shocks, the shorter the rising time of the SSC, and that significantly slanted IP shocks may lead to a delay in the rise of the SSC. Russell et al (1992Russell et al ( , 1994 have found that the square root of the dynamic pressure (P dyn ) of IP shocks has a high correlation with SSCs. They also found that the response differs according to the local time and the direction of the IMF.…”
Section: Introductionmentioning
confidence: 99%
“…They also investigated effects of speed and direction of IP shocks on SSC rise times and found that the faster IP shocks, the shorter the rising time of the SSC, and that significantly slanted IP shocks may lead to a delay in the rise of the SSC. Russell et al (1992Russell et al ( , 1994 have found that the square root of the dynamic pressure (P dyn ) of IP shocks has a high correlation with SSCs. They also found that the response differs according to the local time and the direction of the IMF.…”
Section: Introductionmentioning
confidence: 99%
“…Present analysis indicates that the driven reconnection is a possible candidate for triggering the BBFs. The driving force can be either pressure pulses (Russel et al, 1994) or quasi-steady fluctuations in the solar wind. However, observational constraints on the driving force and subsequently on the fluctuation amplitude as well as features like the local organisation of BBF events should be incorporated in a self-consistent model and the present model does not include these features.…”
Section: Discussionmentioning
confidence: 99%
“…There have been various models proposed so far for the bursty bulk flows. Russel et al (1994) suggested that BBFs can be triggered by the sudden changes in solar wind dynamic pressure. Lakhina (1992Lakhina ( , 1996 proposed a mechanism for BBFs based on the bursty driven reconnection in the magnetotail.…”
Section: Introductionmentioning
confidence: 99%
“…The auroral electrojet has been observed for many years [Kisabeth and Rostoker, 1971;Akasofu, 1977]. It has been found that the auroral electrojet occurs in response to variations of solar wind pressure [Russell et al, 1994] and in association with magnetospheric particle precipitation [Sandholt et al, 1994].…”
Section: Introductionmentioning
confidence: 99%